Una propuesta para la introducción del concepto energía en el Bachillerato - Hierrezuelo Moreno, José; Molina, E. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper settles the foundations of a proposal for the introduction of the concept of energy in secondary teaching and analyses the results obtained.